Dilution effect and identity effect by wildlife in the persistence and recurrence of bovine tuberculosis - HUANG, Z. Y. X.; XU, C.; VAN LANGEVELDE, F.; PRINS, H. H. T.; BEN JEBARA, K.; DE BOER, W. F. (Parasitology, 2014)
Current theories on disease-diversity relationships predict a strong influence of host richness on disease transmission. In addition, identity effect, caused by the occurrence of particular species, can also modify disease risk. We tested the richness effect and the identity effects of mammal species on bovine tuberculosis (bTB), based on the regional bTB outbreak data in cattle from 2005–2010 in Africa. Besides, we also tested which other factors were associated with the regional bTB persistence and recurrence in cattle. Our results suggested a dilution effect, where higher mammal species richness (MSR) was associated with reduced probabilities of bTB persistence and recurrence in interaction with cattle density. African buffalo had a positive effect on bTB recurrence and a positive interaction effect with cattle density on bTB persistence, indicating an additive positive identity effect of buffalo. The presence of greater kudu had no effect on bTB recurrence or bTB persistence. Climatic variables only act as risk factors for bTB persistence. In summary, our study identified both a dilution effect and identity effect of wildlife and showed that bTB persistence and recurrence were correlated with different sets of risk factors. These results are relevant for more effective control strategies and better targeted surveillance measures in bTB.